2018
DOI: 10.1002/cmdc.201700628
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Structure–Activity Relationships with Three‐Dimensional Matched Molecular Pairs—A Review

Abstract: A matched molecular pair (MMP) consists of two small molecules that differ by a few atoms only. The minor structural difference between the molecules allows a detailed analysis of changes in properties. Three-dimensional (3D) MMPs extend the concept of chemical similarity by spatial similarity. Conformations must be generated, and superimpositions have to be calculated. The additional complexity and uncertainty as well as the smaller amount of available experimental data substantially complicates the derivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The structurally similar ligand molecules will bind to the same/identical biological targets and occupy the same region in the binding sites of protein receptors, thereby supporting in designing strategies by shape similarity for their potential application during the drug discovery process [ 37 , 38 ]. This matching between the structurally similar ligand molecules may indicate the similar pharmacological action at the protein receptor.…”
Section: Resultsmentioning
confidence: 99%
“…The structurally similar ligand molecules will bind to the same/identical biological targets and occupy the same region in the binding sites of protein receptors, thereby supporting in designing strategies by shape similarity for their potential application during the drug discovery process [ 37 , 38 ]. This matching between the structurally similar ligand molecules may indicate the similar pharmacological action at the protein receptor.…”
Section: Resultsmentioning
confidence: 99%
“…By applying 3D MMPA methods, systematic analysis of binding affinity data to a specific target was available. 115 Posy et al investigated pairwise activity differences with ligand contextual information. 51 The results showed that compounds with the same binding mode were less likely to experience an activity cliff.…”
Section: ■ Practical Applications Of Mmpamentioning
confidence: 99%
“…These findings have implications for drug repositioning efforts. By applying 3D MMPA methods, systematic analysis of binding affinity data to a specific target was available . Posy et al investigated pairwise activity differences with ligand contextual information .…”
Section: Practical Applications Of Mmpamentioning
confidence: 99%
“…Pharmacophoric features (PFs) consist of single atoms or sets of atoms based on interaction types, such as hydrogen bonding and lipophilic interactions. Because a pharmacophore can be regarded as an interaction hypothesis, it can be used as a query for screening chemical libraries. …”
Section: Introductionmentioning
confidence: 99%